Land tenure in hydropower development: A review - Ghimire, Subash (Kathmandu University Journal of Science, Engineering and Technology, 2013)
Land tenure issues such as tenure forms and its allocation and land acquisition procedure are not extensively considered in hydropower development. As a result hydropower projects are not sustainable. The main aim of the study is to find the role of land tenure in hydropower development. Desk study is carried out and is followed by the scientific literature review. The study reveals that the concession with broader negotiations and agreements is carried out for interfering the land rights for the construction of hydropower project in Norway because of which the Aurland hydropower project got successful. The capability and economical willingness to include land and environmental issues from the start of the project to operation stage made the development successful while concession is practiced in China without broader negotiations and public participation as in Nu river project. Therefore, a Chinese hydropower concession is controversial. Many of the proposed dam is situated in UNESCO world heritage site and in the conservation area. Nu river project affects number of distinct ethnic groups who maintain their religious and cultural tradition. Resettlement is not possible on this ethnic group because of integration into population of various customs, languages and agricultural tradition. In case of Nepal in general, concessions is not practiced during hydropower development. Transparency in information dissemination, decision making, involvement of key stakeholders on key issues and time bound solution can hardly be found during hydropower development. Mostly, land is expropriated for the development of the hydropower project. The study finds that Land tenure has very important role in hydropower development. Therefore, it should be extensively considered for sustainable development of the hydropower projects. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 101-108 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7332